Introduction to microeconomics - Laidler, David (Harvester Wheatsheaf, 1995)
This edition provides questions to allow self-testing of understanding. Increased coverage of industrial organization and information economics and a substantially increased final part on general equilibrium and welfare covers externalities, public goods and public choice.